Endoscopic Approach to Duodenal Adenomas in Familial Adenomatous Polyposis: A Retrospective Cohort - Garcia,Joana Lemos (2023)
Abstract Introduction: Over 90% of the patients with familial adenomatous polyposis (FAP) will develop duodenal adenomas. Aim: The aim of this study was to evaluate the effectiveness and safety of endoscopic excision of large duodenal adenomas in FAP patients. Methods: All FAP patients from a familial risk clinic submitted to endoscopic therapy for duodenal adenomas ≥10 mm between January 2010 and February 2021 were included. Results: From 151 FAP families, 22 patients (50 lesions) were included: 54.5% female; median follow-up 8.5 (IQR: 5.8-12.3) years after the first endoscopy. First therapeutic endoscopy occurred at a median age of 41.0 years (IQR: 33.0-58.2). Repeat therapeutic endoscopy was required in 54.5% of patients. Median size of the largest adenoma was 15 mm (IQR: 10-18 mm); resection was piece-meal in 63.1% and en bloc in the remaining. In 2 cases, the resection was incomplete (fibrosis due to previous resection and difficult positioning). Complications occurred in 6.3% of the resected lesions (4 patients): 2 immediate (bleeding, perforation); 4 in the first week (1 bleeding, 2 mild pancreatitis, 1 perforation requiring surgery; the latter two after ampullectomy). Histology revealed low-grade dysplasia adenomas in 90.1%; no adenocarcinomas were found. One patient with Spigelman stage IV disease not amenable to endoscopic control underwent elective duodenopancreatectomy (without duodenal cancer). Conclusion: Endoscopic surveillance and treatment of duodenal adenomas in FAP patients was safe and effective in the prevention of duodenal cancer.